Identifying cyber insecurities in trustworthy space and energy sector for smart grids. (July 2021) - Priyadarshini, Ishaani; Kumar, Raghvendra; Sharma, Rohit; Singh, Pradeep Kumar; Satapathy, Suresh Chandra
Research Highlights: Identifying Cyber Insecurities in Trustworthy Space and Energy Sector for Smart Grids Classifying Cyber Insecurities in Trustworthy Space and Energy Sector for Smart Grids, based on their underlying motive. Deploying Multi-Criteria Decision Making tool Analytic Hierarchy Process (AHP), to determine which cyber insecurities contribute the most to these classifications or motives. Abstract: Energy is critical infrastructure, and addressing cybersecurity issues in the energy sector is challenging. Cloud computing has advanced from being a data storage solution to a complex system that enables resource management, workforce management, scalability, flexibility, managing operational expenses, etc. The energies sector relies heavily on critical infrastructure and cloud usage. Hence, there is a simultaneous increase in the insecurities prevailing in both environments. Smart grids are vulnerable to cyber insecurities due to immense networking and data delivery. In this paper, we propose some of these insecurities that prevail in the cloud computing environment (Trustworthy Space) and the energy sector for smart grids. The insecurities are classified based on the motivation behind them. We rely on the Multi-Criteria Decision Making (MCDM) tool, Analytic Hierarchy Process (AHP) to determine how these insecurities affect smart grids. As AHP exhibits priority, we can successfully verify the contributory insecurity for every classification. Graphical Abstract: Image, graphical abstract